Implementación de los Compliance Programs y sus efectos de exclusión o atenuación de responsabilidad penal de los sujetos obligados. Actualidad a partir de la Ley 30424, el Decreto Legislativo 1352 y el Proyecto de Reglamento de la Ley 30424. - Reyna Alfaro, Luis Miguel (2018)
Compliance is a topic of undeniable topicality. His initial transfer from bussiness ethics to corporate law and then to criminal law determines the need to recognize his capacity for performance. In our analysis we try to propose an initial assessment of the penal legal significance of the implementation of Compliance programs in the face of the possible criminological foundation of its use, an edge barely recognized in our countries of well-known anti-empirical tradition.